Bullying in school and cyberspace: Associations with depressive symptoms in Swiss and Australian adolescents - Cross, Donna (2010)
Background Cyber-bullying (i.e., bullying via electronic means) has emerged as a new form of bullying that presents unique challenges to those victimised. Recent studies have demonstrated that there is a significant conceptual and practical overlap between both types of bullying such that most young people who are cyber-bullied also tend to be bullied by more traditional methods. Despite the overlap between traditional and cyber forms of bullying, it remains unclear if being a victim of cyber-bullying has the same negative consequences as being a victim of traditional bullying. Method The current study investigated associations between cyber versus traditional bullying and depressive symptoms in 374 and 1320 students from Switzerland and Australia respectively (52% female; Age: M = 13.8, SD = 1.0). All participants completed a bullying questionnaire (assessing perpetration and victimisation of traditional and cyber forms of bullying behaviour) in addition to scales on depressive symptoms. Results Across both samples, traditional victims and bully-victims reported more depressive symptoms than bullies and non-involved children. Importantly, victims of cyber-bullying reported significantly higher levels of depressive symptoms, even when controlling for the involvement in traditional bullying/victimisation. Conclusions Overall, cyber-victimisation emerged as an additional risk factor for depressive symptoms in adolescents involved in bullying